Phytochemicals from Pyrrosia longifolia (Burm. f.) C.V. Morton with antibacterial activity - Hilwan Yuda Teruna; Rohimatul Khodijah; Neni Frimayanti; Rudi Hendra (Research in Pharmaceutical Sciences)
Background and purpose: Pyrrosia longifolia is one of the medicinal plants in Indonesia. However, it has received little attention regarding pharmacological properties and phytochemicals. This study aimed to isolate bioactive compounds and evaluate their antibacterial activities. Experimental approach: The secondary metabolites were isolated using a bioassay-guided approach. The aerial part was macerated in methanol and the crude methanol was partitioned with organic solvents to obtain n-hexane, dichloromethane, ethyl acetate, and water extracts. The ethyl acetate extract was purified using chromatography procedures, yielding six chemicals, and their structures were determined using spectroscopy. The antibacterial activity of the compounds was evaluated. Findings/Results: Six secondary phytochemical metabolites were identified including naringin (1), catechin (2), quercetin (3), rutin (4), kaempferol (5), and mangiferin (6). The absolute configurations of compounds 1 and 2 were ascertained using electronic circular dichroism as 2S for naringin and 2R, 3S for catechin. The compounds exhibited antibacterial activity against several pathogenic bacteria, with MIC and MBC values ranging from 7.8 to 250 μg/mL. Computational investigations of these compounds revealed a substantial affinity for bacterial receptors’ active and allosteric regions. Furthermore, rutin exhibited the capacity to reduce the activity of β-ketoacyl-acyl carrier protein synthase III, enhancing its antibacterial effectiveness. Conclusion and implications: The in-vitro assessment revealed that the six identified compounds possess a wide range of antibacterial activity, which was corroborated by in-silico analyses. However, further investigation is required to back up the conclusion of this study.